Aloperine Protects Mice against DSS-Induced Colitis by PP2A-Mediated PI3K/Akt/mTOR Signaling Suppression - Fu, Xiaoxia; Sun, Fei; Wang, Faxi; Zhang, Junai; Zheng, Biying; Zhong, Jixin; Yue, Tiantian; Zheng, Xuebao; Xu, Jun-Fa; Wang, Cong-Yi (Mediators of Inflammation, 2017)
Colitis is a major form of inflammatory bowel disease which involved mucosal immune dysfunction. Aloperine is an alkaloid isolated from the shrub Sophora alopecuroides L. and has been recognized as an effective treatment for inflammatory and allergic diseases. The present study aimed to examine the molecular mechanisms underlying aloperine-mediated colitis protection. We found that aloperine treatment improved colitis induced by dextran sodium sulfate (DSS) based on body weight, disease activity index, colonic length, and spleen index. Aloperine also effectively attenuated DSS-induced intestinal inflammation based on the pathological score and myeloperoxidase expression and activity in colon tissues. In addition, aloperine regulated T-cell proportions and promoted Foxp3 expression in the spleens and mesenteric lymph nodes of DSS-induced colitis mice and in the spleens of the Foxp3GFP mice. Aloperine inhibited Jurkat and mouse naïve T-cell apoptosis. Furthermore, aloperine inhibited PI3K/Akt/mTOR signaling and upregulated PP2A expression in the DSS-induced colitis mice and in Jurkat cells, but LB-100 (PP2A inhibitor) resulted in an elevated Akt activity in Jurkat cells, activated T-cells, and human splenic mononuclear cells. Aloperine inhibited T-cell and lymphocyte proliferation, but LB-100 reverse these effects. In conclusion, aloperine regulates inflammatory responses in colitis by inhibiting the PI3K/Akt/mTOR signaling in a PP2A-dependent manner.